Sosialisasi Konservasi Hutan Mangrove Berbasis Syariah kepada Masyarakat Pesisir di Gampong Kuala Bubon Kecamatan Samatiga Kabupaten Aceh Barat Propinsi Aceh - Mohamad Gazali; Supriadi Supriadi; Muhammad Nurdin; Muhammad Ilham (Universitas Teuku Umar, 2017)
The coastal Area of Kuala Bubon subdistrict, Samatiga District, West Aceh regency, Aceh Province have several mangrove species including Rhizoporastylosa, RhizoporaapiculataBI andNypa fruticans. Aceh is popular with epithet “ Serambi Mekkah” that is the only province in Indonesia that stipulated sharia to the Aceh community. The local goverment regulation was designed according to islamic sharia. Dependent rule in Aceh Area is named Qanun Aceh. Therefore, it is neccessary to undertaken a approach to change gradually their mindset for keeping mangrove ecosystem through dakwah media and real action. The main problem in Kuala Bubon’s community are lack of awareness and wide understanding regarding management of mangrove forest sustainable. Otherwise, the involvement and socialization of mangrove conservation with periodically with coastal community is still poor that undertaken by stakeholder. The purpose of this program is to give undertanding and knowledge regarding forest mangrove conservation that involved cleric and community figure. These programs that is conducted including seedings from natural. Subsequently, we involved local community in da’wah that is conducted in Ramadhan Month. Forincreasing the knowledge about mangrove conservation, we conducted extension activity that attended by local government and coastal community. According to deliberation, we conducted the planting of mangrove seeds in nearby Nurul Iman mosque as green belt. Otherwise, we also give them sedekah to Nurul Iman organizer for development of Nurul Iman Mosque as da’wah media for Kuala Bubon’s community.